2019
DOI: 10.3389/fimmu.2019.02279
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Promote Kidney Graft Rejection Independently of Cyclosporine A Therapy

Abstract: Natural Killer (NK) cells have recently been recognized as key players in antibody-mediated chronic allograft failure, thus requiring a comprehensive understanding whether NK cells can escape conventional immunosuppressive regimens. Influence of cyclosporine A (CyA) on NK cell function was studied in a mouse model of allogeneic kidney transplantation (KTX, BALB/c to C57BL/6). Recipients were treated daily with CyA (10 mg/kg) for seven or 14 days for long term survival (day 56). Administration of CyA in recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…101 AMR leads to graft loss via complement deposition, recruitment of NK cells, monocytes and macrophages which contribute towards fibrin formation, endothelial cell damage and eventually interruption of vascular function. 98,102 Anti-HLA antibodies identified in CHI could be likened to these DSAs, especially as complement, monocytes and macrophages also appear to play a key role in its pathophysiology. 4,63 However, as the placenta is known to express only the least polymorphic of HLA molecules with low immunogenicity, it is unclear how anti-HLA antibodies may be detrimental when not deemed so in normal healthy pregnancy.…”
Section: S Imil Aritie S B E T Ween Allog R Af T Re Jec Ti On and Chimentioning
confidence: 99%
“…101 AMR leads to graft loss via complement deposition, recruitment of NK cells, monocytes and macrophages which contribute towards fibrin formation, endothelial cell damage and eventually interruption of vascular function. 98,102 Anti-HLA antibodies identified in CHI could be likened to these DSAs, especially as complement, monocytes and macrophages also appear to play a key role in its pathophysiology. 4,63 However, as the placenta is known to express only the least polymorphic of HLA molecules with low immunogenicity, it is unclear how anti-HLA antibodies may be detrimental when not deemed so in normal healthy pregnancy.…”
Section: S Imil Aritie S B E T Ween Allog R Af T Re Jec Ti On and Chimentioning
confidence: 99%
“…Most transplant patients maintain a course of immunosuppression to inhibit donor-reactive T cell responses that includes an anti-proliferative drug and a calcineurin inhibitor. Whether these immunosuppressive drugs inhibit NK cell activation is not as clear with in vitro and in vivo studies yielding unclear conclusions their efficacy on NK cell activation (56)(57)(58). The results of the current study suggest that identification of myeloid cell targets will also attenuate acute ABMR.…”
Section: Discussionmentioning
confidence: 85%
“…In solid organ transplantation, a large number of cells expressing foreign human leukocyte antigens (HLA) are introduced into the transplant recipient. Mouse models have shown that alloreactive NK cells can be a notable contributor to kidney allograft rejection ( 30 ). Further, alloreactive NK cells seemed to contribute allograft rejection in human liver transplantation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%